Sulfates in Completely Recyclable Concrete and the effect of CaSO4 on the clinker mineralogy. (15th April 2017) - De Schepper, Mieke; Van den Heede, Philip; Arvaniti, Eleni C.; De Buysser, Klaartje; Van Driessche, Isabel; De Belie, Nele
Highlights: Completely Recyclable Concrete (CRC) is a potentially sustainable concrete. It implies less use of natural resources and less waste production. Contaminations during the concrete lifespan should not compromise the CRC clinker quality. Higher sulfate content stimulates formation of CaO containing Ca langbeinite and anhydrite. Higher sulfate concentrations stabilize belite at the expense of alite. Abstract: To increase the recycling potential of concrete, Completely Recyclable Concrete (CRC) has been developed to be used as a raw material for cement clinker production. Sulfates may penetrate CRC structures in time and their presence could affect the clinkering process of the eventually obtained CRC rubble. Therefore, the effect of CaSO4 additions on the final CRC clinker mineralogy has been investigated using XRD/Rietveld and SEM/EDX. An increasing sulfate content was found to stimulate the formation of sulfates that incorporate CaO, i.e. calcium langbeinite and anhydrite. Moreover, belite tends to be stabilized at the expense of alite with more SO3 present.